In Vivo and in Vitro Regulation of Syndecan 1 in Prostate Cells by n-3 Polyunsaturated Fatty Acids - Edwards, Iris J. (American Society for Biochemistry and Molecular Biology, 2008)
Syndecan 1 is the major proteoglycan produced by epithelial cells. It is strategically localized at the plasma membrane to participate in growth factor signaling and cell-cell and cell-matrix interactions. Its expression may modulate the properties of epithelial lineage tumor cells in which it is generally down-regulated compared with nontumor progenitors. The present study examined the regulation of syndecan 1 in prostate epithelial cells by n-3 polyunsaturated fatty acids. In prostate tissue of mice, syndecan 1 immunostaining was demonstrated in epithelial cells throughout each gland. In animals fed an n-3 polyunsaturated fatty acid-enriched diet, syndecan 1 mRNA was increased in all prostate glands. In the human prostate cancer cell line, PC-3, delivery of exogenous n-3 (but not n-6) fatty acids resulted in up-regulation of syndecan 1 expression. This effect was mimicked by a peroxisome proliferator-activated receptor (PPAR) γ agonist, troglitazone, and inhibited in the presence of a PPARγ antagonist and in cells transfected with dominant negative PPARγ cDNA. Using a luciferase gene driven either by a PPAR response element or by a DR-1 site present in the syndecan 1 promoter, reporter activation was increased by n-3 low density lipoprotein, docosahexaenoic acid, and troglitazone, whereas activity of a luciferase gene placed downstream of a mutant DR-1 site was unresponsive. These findings indicate that syndecan 1 is up-regulated by n-3 fatty acids by a transcriptional pathway involving PPARγ. This mechanism may contribute to the chemopreventive properties of n-3 fatty acids in prostate cancer.